Managing Outliers in Australian Surgical Clinical Quality Registries - Alun Cameron; Konstance Nicolopoulos; R. James Aitken; Helena Kopunic; Wendy Babidge; Guy J. Maddern (ANZ Journal of Surgery, 2026)
ABSTRACT Clinical quality registries (CQRs) are central to improving surgical safety and quality by enabling systematic monitoring of outcomes and proactive identification of outliers. Published guidelines provide important advice on methods and activities for CQRs. Guideline flexibility allows for the varied and unique requirements of each CQR, but some aspects around guideline implementation are less certain, particularly for outlier management. In order to describe activities in Australia and the UK, searches were undertaken for published examples of CQR analysis and reporting of outliers and the subsequent management of outlier surgeons. There are many examples of high quality CQRs which actively report relevant performance indicators, with dashboards that show inter‐hospital variation including unwarranted (outlier) variance. A small number of reports from the UK provide insight to local responses to suspected outlier status, commonly identifying data errors or systemic failures of local care processes. In Australia, challenges include voluntary participation, incomplete datasets, varied benchmarks, complex governance across public and private systems, and in some the restrictions imposed by qualified privilege. Worryingly, no single body is responsible for the management of the outlier surgeon. Outlier management can build on existing governance practices such as morbidity and mortality meetings and professional development activities. The publication of outlier processes and outcomes provides transparency to participants and closes the feedback loop. Active participation in CQRs and effective local outlier management actions should be encouraged as part of quality improvement, to learn from mistakes, celebrate excellence, and improve patient outcomes.